Literature Review: The Effect of Online Shops on Consumer Shopping Satisfaction - Muhammad Ammar Muhtadi (Eastasouth Institute, 2023)
Technology makes times change, this change will be followed by increasing needs and different desires in the future, especially shopping needs. Online shopping is becoming popular, especially in groups of people who usually use internet services. Online shopping activities can be done through smartphones, tablets, and laptops that are connected to the internet network. Consumer satisfaction is also one of the most important factors in doing business online to be able to win the competition. The purpose of this study is to determine the effect of online shopping on consumer shopping satisfaction accompanied by the factors that make online shopping able to provide satisfaction for consumers. The method used in this research is the literature review method. That is a literature search conducted through Google Scholar. In the early stages of the article search, 52,200 scientific articles were obtained using the keywords